Turning a social character trait phenomenon into a diagnostic web-based measuring instrument using a grounded theory research method - Sheik Said, Normahdiah; Hashim, Mohamad Ghazali; Che Rodi, Rozita; Ab Karim, Siti Sarah (Universiti Putra Malaysia Press, 2013)
The formation of proverbs and phrases into poetic forms with synchronised sentence structures and rhyming expressions through authentic dictions that are engaging and meaningful are the treasures of one’s trait and nation. For some race or ethnic groups it is through these classical works of wisdom that a race or an ethnic group could prevail and remain recognised transcends time and age . A list of 26 basic components of social character traits of the Malays was traced through maxims and literary work s of wisdom. The list of social character traits will just remain a list of compilation to be read and forgotten, just like many others written and compiled by other Malay literary scholars. There is a need to make this list scientifically proven. This paper discusses on how these components were transformed into a measuring instrument through a grounded theory research method. The end product was not only a web-based diagnostic instrument to measure the conformity and deviation of an ethnic group but also a formation of a new theory that could be applied to all other ethnics and related groups in the world today that are interested in knowing and preserving their social character traits.